Thermodynamic description of the plutonium – α-d-isosaccharinic acid system I: Solubility, complexation and redox behavior. (November 2018) - Tasi, A.; Gaona, X.; Fellhauer, D.; Böttle, M.; Rothe, J.; Dardenne, K.; Polly, R.; Grivé, M.; Colàs, E.; Bruno, J.; Källström, K.; Altmaier, M.; et al.
Abstract: The impact of α-d -isosaccharinic acid (HISA), a degradation product of cellulose, on the solubility and redox behavior of hydrous Pu(IV) oxide was investigated from undersaturation conditions under Ar atmosphere in 0.1 m NaCl–NaOH–NaISA solutions. Redox conditions were buffered with hydroquinone (HQ) or Sn(II), resulting in (pe + pHm ) ≈ 9.0 and 1.5, respectively. The influence of ISA on Pu solubility was investigated as function of pHm (8 ≤ pHm ≤ 13) and ligand concentration (10 −6 m ≤ m(ISA)tot ≤ 0.1 m). In-situ X-ray diffraction and X-ray absorption spectroscopic measurements indicate that PuO2 (ncr, hyd) controls the solubility of Pu in all investigated systems. Presence of ISA poses an increase in plutonium solubility by up to 2.5 log-units. In HQ systems, slope analysis of solubility data in combination with solid phase characterization and density functional theory calculations resulted in chemical and thermodynamic models including the predominance of Pu(IV)(OH)3 ISA–H – and Pu(IV)(OH)3 ISA–2H 2– complexes below and above pHm ≈ 12, respectively. In Sn(II) systems with pHm < 11.5, a reductive dissolution occurs involving the formation of Pu(III)(OH)ISA–H (aq). Experimental observations suggest also that Pu–ISA colloids importantly contribute to the overall Pu concentration in solution, both in HQ and Sn(II) systems. Although this process is not included in the thermodynamic model derived, it cannot be neglected for estimating Pu solubility limits under these conditions. This work provides the most comprehensive thermodynamic dataset available to date for the system Pu 3+ –Pu 4+ –OH – –Cl – –ISA – –H2 O(l) valid under a wide range of conditions relevant for nuclear waste disposal. Graphical abstract: The impact of α-D-isosaccharinic acid (HISA, main degradation product of cellulose) on the solubility, complexation and redox behavior of plutonium is evaluated using a combination of solubility experiments, advanced spectroscopic techniques and DFT calculations. Three new Pu-ISA complexes are identified, and the most comprehensive thermodynamic dataset available to date for the system Pu(III)-Pu(IV)-ISA is derived. This model is valid under a wide range of boundary conditions relevant in the context of nuclear waste disposal. Highlights: Solubility of PuO2 (ncr, hyd) increases up to 2.5 log10 -units in the presence of ISA. ISA forms stable complexes with Pu(III/IV)aq under alkaline, reducing conditions. ISA enhances the fraction of colloidal Pu species in solution. DFT provides relevant insights in the structure of Pu(III/IV)–ISA complexes. A thermodynamic model is derived for the system Pu 3+ –Pu 4+ –OH – –Cl – –ISA – –H2 O(l).